AMNESIA IN BEFORE I GO TO SLEEP NOVEL BY S. J. WATSON - At Taba', Wildan Baihaqi Yusuf; Rahayu, Anik Cahyaning (COMMUNITY OF RESEARCH LABORATORY SURABAYA, 2024)
This study explores the symptoms, causes, and impacts of Christine Lucas's amnesia as depicted in Before I Go to Sleep novel by S. J. Watson, using a psychological approach and descriptive qualitative method. Employing Rajesh Kumar’s theory of amnesia, the study focuses on amnesia linked to psychological problems. Christine exhibits four key symptoms: anterograde symptom, where she cannot form new memories and wakes up daily with no recollection of recent events; retrograde symptom, where she forgets her adult life and retains only childhood memories; confabulation symptom, where she fills memory gaps with imagined or false memories; and disorientation symptom, where she is confused about her identity and surroundings each morning. Her condition results from head injuries and oxygen deprivation caused by a violent assault and subsequent coma. The impacts of her amnesia are profound, including a loss of identity, as she struggles with her roles as a wife and mother; strained relationships, culminating in her husband divorcing her despite his love; and difficulty distinguishing between reality and fantasy, particularly during episodes of confabulation. The findings highlight how Christine’s memory loss fundamentally shapes her life and identity, underscoring the deep psychological and relational consequences of her condition.